Measurement of isotopically‐exchangeable Zn in Zn‐deficient paddy soil - Izquierdo, M.; Impa, S.M.; Johnson-Beebout, S.E.; Weiss, D.J.; Kirk, G.J.D. (Wiley, 2016)
The changes in soil chemistry following submergence of a soil for rice production result in zinc (Zn) being immobilized in very insoluble forms. Consequently, Zn deficiency is widespread in rice crops and in human populations that subsist on rice. We explored the use of stable isotopic dilution assays for assessing Zn dynamics in submerged paddy soil with two types of strongly Zn‐deficient soil for rice cultivation in the Philippines. We optimized the isotope enrichment, electrolyte and equilibration time to measure isotopically‐exchangeable Zn (E‐values) without changing redox conditions. Available Zn was rapidly and strongly immobilized following submergence, which was controlled by CO2 accumulation. Addition of the isotopic tracer before submergence produced unreliable E‐values because irreversible immobilization of the tracer progressed faster than isotopic exchange. Addition of the tracer to already reduced soil produced stable E‐values for tracer–soil contact of up to 1 week. Longer periods produced unreliable E‐values because of continuing irreversible fixation of the tracer. We discuss the implications for applications of isotopic dilution methods to measure trace‐element dynamics in submerged soil.